(Rainforest) reptiles and amphibians - Parker, Edward (Hodder Wayland London, 2003)
The tropical rainforests of the world are home to some of the reptiles and amphibians. This book takes a look at some of these reptiles and amphibians that live in the rainforest, and at their homes, food and threats. It highlights the relationships of rainforest reptiles and amphibians to those living in other habitats.